Doctors’ perceived working conditions, psychological health and patient care: a meta-analysis of longitudinal studies - Teoh, Kevin; Singh, Jasmeet; Medisauskaite, Asta; Hassard, Juliet (Occupational and Environmental Medicine, 2023)
Objectives Studies have demonstrated an association between doctors’ perceived working conditions, and their psychological well-being and patient care. However, few have examined inter-relationships among these three domains, and even fewer using longitudinal designs. Using meta-analytical structural equation modelling, we tested longitudinal relationships among doctors’ perceived working conditions, their psychological well-being and patient care. We further tested if doctors’ psychological well-being mediates the relationship between perceived working conditions and patient care.Methods We carried out a systematic review using Academic Search Premier, Business Source Premier, PsycInfo, PsycArticles and Medline for the 20-year period between January 2000 and the start of the pandemic (January 2020). We included studies with practising doctors as participants, and that reported a quantifiable bivariate effect size between at least two of the three constructs of interest—perceived working conditions (ie, job demands, job resource), psychological well-being (ie, emotional exhaustion, work engagement) and patient care (ie, clinical care, patient safety). We pooled relationship effect sizes using random-effects meta-analysis, before testing for indirect effects using two-stage structural equation modelling.Results Twenty-three samples from 11 countries representing 7275 doctors were meta-analysed. The results indicated that job resources predicted work engagement (ρ=0.18; 95% CI 0.11 to 0.24) and emotional exhaustion (ρ=−0.21; 95% CI −0.31 to −0.11), while job demands predicted emotional exhaustion (ρ=0.27; 95% CI 0.17 to 0.36). Better clinical care was also associated with higher levels of job resources (ρ=0.16; 95% CI 0.04 to 0.29), and lower levels of emotional exhaustion (ρ=−0.21; 95% CI −0.37 to −0.12) and job demands (ρ=−0.27; 95% CI −0.43 to −0.10). Both factors of the work environment were associated with clinical care through doctors’ emotional exhaustion, but there were insufficient studies to test the indirect effects for work engagement or patient safety.Conclusion Our results demonstrate the need for a systems perspective to address working conditions to support both doctors’ psychological well-being and patient care. Interventions should target doctors’ job resources as they are more strongly associated with psychological well-being. However, given that job demands were strongly associated with emotional exhaustion, and in turn, clinical care, there is a need to better manage doctors’ workload, conflict and pressure to support the current psychological well-being crises among this occupational group.PROSPERO registration number CRD42020189070.